2015
DOI: 10.1186/s13568-015-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Maize growth promotion by inoculation with Azospirillum brasilense and metabolites of Rhizobium tropici enriched on lipo-chitooligosaccharides (LCOs)

Abstract: There is an increasing interest in the development and use of inoculants carrying plant growth-promoting bacteria (PGPB) in crops of agronomic interest. The great majority of the inoculants commercialized worldwide contain rhizobia for legume crops, but the use of PGPB as Azospirillum spp. for non-legume is expanding, as well as of inoculants combining microorganisms and microbial metabolites. In this study we evaluated the effects of inoculants containing Azospirillum brasilense with or without metabolites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 55 publications
1
39
1
Order By: Relevance
“…Positive results of increment of height, stem diameter and shoot dry matter in maize were observed by Mazzuchelli et al (2014), for simultaneous use of Bacillus subtilis and Azospirillum brasilense, and by Dartora et al (2013), for the association of Azospirillum brasilense and Herbaspirillum seropedicae. In addition, Marks et al (2015) conducted a study about inoculation of Azospirillum brasilense and Rhizobium tropici metabolites in maize and observed increase in shoot dry matter, grain yield and N accumulation. The authors also attributed these results to the metabolites that are produced by rhizobia and act in the promotion of plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Positive results of increment of height, stem diameter and shoot dry matter in maize were observed by Mazzuchelli et al (2014), for simultaneous use of Bacillus subtilis and Azospirillum brasilense, and by Dartora et al (2013), for the association of Azospirillum brasilense and Herbaspirillum seropedicae. In addition, Marks et al (2015) conducted a study about inoculation of Azospirillum brasilense and Rhizobium tropici metabolites in maize and observed increase in shoot dry matter, grain yield and N accumulation. The authors also attributed these results to the metabolites that are produced by rhizobia and act in the promotion of plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is inferred that the application of Azospirillum is also responsible for higher rates of absorption of water and minerals by the plant (Dardanelli et al, 2008) and higher tolerance to abiotic stresses, such as drought and salinity (Zawonski et al, 2011). The relationship between different soil microorganisms and the role of metabolites secreted by them on growth of other surrounding microbial species and plants has been the subject of numerous studies (Marks et al, 2015;Fukami et al, 2016;Fukami et al, 2017), and according to Bashan and de-Bashan (2010), due to the wide array of mechanisms proposed for stimulation of plant growth by Azospirillum spp., probably this bacteria promoves multiple mechanisms that might act either in a cumulative or sequential pattern.…”
Section: Technical Analysis: Corn Grain Yieldmentioning
confidence: 99%
“…The technology of inoculation of non-legumes with non-symbiotic plant growth-promoting bacteria (PGPB), whose main representative is Azospirillum spp. is also being increasingly adopted in several countries, especially for crops such as corn and wheat (Díaz-Zorita & Fernandez-Canigia, 2009;Hartmann & Bashan, 2009;Marks et al, 2015). The analysis of results from a large number of field trials with various non-legume crops, conducted worldwide over 20 years, under different soil and weather conditions, has demonstrated that yield increases of up to 30% could be obtained 70% of the time (Fukami et al, 2016;Fukami et al, 2017) in response to inoculation with Azospirillum.…”
Section: Introductionmentioning
confidence: 99%
“…Azospirillum species have been widely reported to induce the formation of lateral roots and abundant radical pili (creating higher rizhospheric volumes) in several plant families by biosynthesis of growth promoting substances (Marks et al, 2015).…”
Section: Effect Of Rhizobacteria Inoculation In Vivo On Lettuce Earlymentioning
confidence: 99%